Characteristic of Patients with Gastric Perforation due to Peptic Ulcer in Dr. Soetomo General Hospital Surabaya in the Period of January - December 2016 - Esthiningrum Dewi Agustin; Mamiek Dwi Putro; Herry Purbayu (JBN (Jurnal Bedah Nasional), 2019)
Aim: This study aims to study the profile of patients with gastric perforation caused by peptic ulcer. Method: This is a retrospective study by obtaining patients data from medical records in the Medical Record Centre of Dr. Soetomo General Hospital during the period of January - December 2016 and analyzed descriptively. Result: 66 patients were identified (45 male and 21 female), most of them were between age 60 - 69 years old, and live in Surabaya (45.45%). 30.3% of patients No malignancy was found during the anatomic-pathological examination. 30.3% of patients have a long term NSAID taking, while 53.03% of patients came with a habit of traditional medicine consumption. Perforations were mostly located 1 - 5 cm pre-pyloric and between the range 0.5 - 1 cm in diameter (56.6% and 69.7%, respectively). Conclusion: With the lack of information, it still needs further studies with more completed data for better accuracy.